Preference of Tourists toward Peace Tourism Product for Ground Zero Monument in Kuta Bali - Ariana, Nyoman; Sukana, Made; Ariana, I Nyoman Jamin (Journal of Indonesian Tourism and Development Studies, 2016)
The purpose of this study is to analyze the preferences of tourists toward the development of Ground Zero Monument as a peace tourism product in Kuta Bali. Samples of research is determined by purposive sampling, as many as 100 tourists. Data was analyzed by method of conjoint analysis. The results showed that it is necessary to offer statue of monument (miniature) and the history book of monument as a souvenir for the tourists, provide adequate monument facilities, give a special place for tourists to pray, package products to accommodate the values of peace symbols, design package monument tour that is interesting for the tourist by providing interpreters (guides to explain the monument), and it is not necessary to provide the transportation for the tourist because they are more likely to use private transport. While the level of interest rates in the product of peace tourism in Monument Ground Zero from highest to lowest based on the attribute utility value is as follows: souvenirs (16.509%), physical attractiveness (15.775%), services (14.889%), non-physical attractiveness (14.461%), facilities (13.820%), attractions (12.648%), and transports (11.898).Keywords: Monument, Peace, Preferences, Tourism, Tourists.